2010
DOI: 10.1186/1743-422x-7-110
|View full text |Cite
|
Sign up to set email alerts
|

Comparative whole genome sequence analysis of wild-type and cidofovir-resistant monkeypoxvirus

Abstract: We performed whole genome sequencing of a cidofovir {[(S)-1-(3-hydroxy-2-phosphonylmethoxy-propyl) cytosine] [HPMPC]}-resistant (CDV-R) strain of Monkeypoxvirus (MPV). Whole-genome comparison with the wild-type (WT) strain revealed 55 single-nucleotide polymorphisms (SNPs) and one tandem-repeat contraction. Over one-third of all identified SNPs were located within genes comprising the poxvirus replication complex, including the DNA polymerase, RNA polymerase, mRNA capping methyltransferase, DNA processivity fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 71 publications
0
38
0
Order By: Relevance
“…In previous studies, the A314V change (Table 1) was found in VACV HPMPC R (i) as a single point mutation (10) or (ii) associated with other amino acid modifications, including H296Y, H319N, S338F, and R604S (43). In HPMPC R MPXV, the mutated residue A314V has been reported with another amino acid change at position 684 (A684T), and they were concomitant to A613T and T808M (30). The A684V change has already been selected with another amino acid change at position 314 (A314T), and these mutations were involved in (S)-HPMPC and (S)-HPMPDAP resistance development in VACV (Table 1) (4,32).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous studies, the A314V change (Table 1) was found in VACV HPMPC R (i) as a single point mutation (10) or (ii) associated with other amino acid modifications, including H296Y, H319N, S338F, and R604S (43). In HPMPC R MPXV, the mutated residue A314V has been reported with another amino acid change at position 684 (A684T), and they were concomitant to A613T and T808M (30). The A684V change has already been selected with another amino acid change at position 314 (A314T), and these mutations were involved in (S)-HPMPC and (S)-HPMPDAP resistance development in VACV (Table 1) (4,32).…”
Section: Discussionmentioning
confidence: 99%
“…To measure the growth rates of recombinant viruses, HEL cells were allowed to grow until confluence in 24-well plates and infected with the strain of interest at an MOI of 0.01. At different time points, i.e., 3,6,9,24,30,48, and 72 h postinfection, the cells were harvested (in triplicates), and the viruses were released by freeze-thawing for further titrations by plaque assays in HEL cells. Virus titers, expressed in PFU/ml, are presented as the means from two independent experiments.…”
Section: Drug Resistance In Camelpox and Vaccinia Virusesmentioning
confidence: 99%
See 2 more Smart Citations
“…Compounds that show promise in preclinical or clinical settings are the cidofovir derivative CMX001 (24), which is a nucleoside analog, and ST-246 (12,13), which has a unique mechanism of action in preventing viral egress from infected cells. With the majority of inhibitors, including CMX001 and ST-246, viral resistance is achieved rapidly in cell culture (1,9,33). As with many antimicrobial strategies, effective treatment is likely to require combination therapy.…”
mentioning
confidence: 99%